Resisting autocratization: the protest–repression nexus in Hong Kong's Anti-ELAB Movement. (3rd December 2021) - Tung, Hans H.; Kasuya, Yuko
Abstract: This introductory essay outlines the core themes of the special issue on the rise and fall of Hong Kong's Anti-Extradition Law Amendment Bill Movement. In the essay, we highlight several theoretical and empirical contributions the featured papers make to our understanding of the protest–repression nexus from the onset of the movement to the imposition of the National Security Law. First, we describe the political and social contexts of the movement. Second, we present our empirical findings on Hong Kongers' political preferences. Finally, we highlight new research avenues arising from this special issue.